Regularity of solutions of Degenerate Quasilinear Parabolic Equations (weighted case) - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish the inner regularity of solutions and their derivatives with respect to spatial coordinates for a degenerate quasilinear parabolic equation of the second order.